Falsely decreased ferritin concentrations in two patients with haemophagocytic lymphohistiocytosis: A case report. (January 2019) - Roozen, Geert; Revet, Ingrid; Raymakers, Reinier; Kemperman, Hans
The high-dose hook effect, or prozone effect, can lead to negative or falsely lowered plasma ferritin results. Here, cases of a 16-year-old boy and a 70-year-old woman with haemophagocytic lymphohystiocytosis with extremely high concentrations of plasma ferritin (387, 000  μ g/L and 138, 000  μ g/L, respectively) are presented. In both cases, falsely lowered ferritin results were reported without any analyser flag. This article emphasizes the importance of recognition of the high-dose hook effect, since a watertight solution is lacking.